The Application of Fisher Scoring Algorithm on Parameter Estimation of Normal Distributed Data - Purba, Switamy Angnitha (Journal of Research in Mathematics Trends and Technology, 2021)
In statistics, parameter estimation is the estimation of a population using sample data. A population data certainly has a certain distribution. Fisher Scoring is a form of Newton's method which is commonly used in solving the maximum likelihood equation. The focus of this research is to estimate distributed data using the fisher scoring algorithm